Annual Report on Exchange Arrangements and Exchange Restrictions 1959. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1959)
This paper discusses economic and financial difficulties that will undoubtedly continue to confront them, although it is to be expected that renewed expansion in world trade will ease the decline in export earnings which they have recently suffered. Much effort will be needed nationally and internationally to create the conditions which will enable these countries to reap the full advantages of growth combined with domestic stability and external equilibrium. In this endeavor, those countries which conduct their transactions in convertible currencies, and which have relatively simple exchange systems, will be in a better position to cope with the financial problems arising out of urgent needs for development. Although many obstacles remain, there is in the world today an increased understanding of the issues involved, and the possibility of achieving the full benefits of a multilateral system is now greater than at any previous time in the IMF's history.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet